The Relationship Between Knowledge, Attitudes and Actions of Mothers in Feeding Children Aged 6-24 months in The Segiri Health Centre Area, Samarinda City - Sari, Rita Puspa; Ruminem, Ruminem; Sholichin, Sholichin; Khumaidi, Khumaidi (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
Background: Complementary feeding is done to support the growth and development of children through adequate nutritional needs, stimulation needs from both gross motor and fine motor, as well as adequate emotional needs and affection. A mother must be able to introduce a side intake known as complementary food or complementary food to breast milk right from the age of 6 to 24 months. Objective: To obtain the results of research in the form of Analysis of the Relationship between Knowledge, Attitudes and Actions of Mothers in providing complementary food for children aged 6-24 months in the Segiri Health Centre working area of Samarinda City. Methods: The research design used is Descriptive Correlation with Crossectional Study research design. Information and data in this study were obtained through filling out questionnaires by respondents.  The sample used in this study amounted to 81 mothers with the criteria that mothers have children aged 6-24 months who live in the Segiri Samarinda Health Centre area, mothers can read and write and are willing to be respondents. Results  of Research: The results of data analysis of the variables in this study obtained the results of the ρ-value of 0.033 (<0.05) which can be interpreted that there is a relationship between the variables of Knowledge, Attitude and Action in providing complementary foods to children aged 6-24 months. Conclusion: The information obtained from the research that has been carried out is that there is a significant relationship between knowledge, attitudes and actions of mothers in providing complementary foods to children aged 6-24 months in the Segiri Samarinda Health Centre area. Suggestion: Mothers who have children aged 6-24 months, in order to increase knowledge about how to process and provide appropriate complementary foods to children, Positive attitudes must be maintained in order to practice giving complementary foods to their children correctly. Future research should identify other factors that influence the provision of complementary foods to children aged 6-24 months